2020
DOI: 10.3329/cmoshmcj.v19i2.50017
|View full text |Cite
|
Sign up to set email alerts
|

Top Five Causes of Neck Mass in Chattogram

Abstract: Background: Identifying top problems in any discipline is very important for diagnosis and effective management. Unfortunately there is a knowledge gap in Chattogram, Bangladesh. To fill up the gap we have conducted the study. Materials and methods : It was a retrospective study based on hospital records of Chattogram General Hospital from January 2017 to December 2017. All (104) cases with neck mass were included. Age, sex, clinical diagnosis, histo-pathological diagnosis and management were noted. Data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 1 publication
2
2
0
Order By: Relevance
“…7 Previously, Chowdhury et al observed that histopathologically TB Lymphadenopathy was the top-ranking neck mass found in all age groups. 12 Inflammatory lesions are the most common neck masses in many studies from Bangladesh and neighbouring countries, supported by our research. 5,7,12 Inflammatory lesions occur among neck masses in developing countries, while congenital and neoplastic masses are most common in developed countries.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…7 Previously, Chowdhury et al observed that histopathologically TB Lymphadenopathy was the top-ranking neck mass found in all age groups. 12 Inflammatory lesions are the most common neck masses in many studies from Bangladesh and neighbouring countries, supported by our research. 5,7,12 Inflammatory lesions occur among neck masses in developing countries, while congenital and neoplastic masses are most common in developed countries.…”
Section: Discussionsupporting
confidence: 80%
“…12 Inflammatory lesions are the most common neck masses in many studies from Bangladesh and neighbouring countries, supported by our research. 5,7,12 Inflammatory lesions occur among neck masses in developing countries, while congenital and neoplastic masses are most common in developed countries. 3 Neoplastic masses are the most frequent neck mass in patients aged 40 or over, while inflammatory masses are the most common in children due to upper respiratory tract infections.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Raw RNA-Sequence reads of different tissues of Tenualosa ilisha have been deposited in the NCBI Sequence Read Archive (SRA) database under the NCBI Bioproject ( https://www.ncbi.nlm.nih.gov/bioproject/ ) with accession PRJNA850620 22 . Final set of transcripts have been submitted to NCBI Transcriptome Shotgun Assembly (TSA) database ( https://www.ncbi.nlm.nih.gov/genbank/tsa/ ) under the accession no GKAU00000000 23 . Raw assembly data, annotation file and Transdecoder predicted peptide files have been deposited in Figshare 24 .…”
Section: Data Recordsmentioning
confidence: 99%